Atuação da enfermagem na rede básica de saúde do município de Rio Grande - Branco, Zelionara Pereira; Gomes, Maria Regina de Oliveira; Juliano, Ana Lúcia Godoy; Hamilton, Clarice Ana Dalla Vecchia (VITTALLE - Revista de Ciências da Saúde, 2017)
Ver no documento